In Honour of the Seventy-fifth Birthday of Professor C. J. Gadd
pp. I-II: Proem in Honour of Professor Emeritus C. J. Gadd, C.B.E., M.A., Hon. D. Litt. Oxon., F.B.A., F.S.A., Membre de l’Institut de France. - all relevant articles Usted suo loco.